Address by J.E.F. Matthews, Ordinary, Upson County, Georgia - Matthews, J.E.F. (United Daughters of the Confederacy, 1908)
A self-published booklet from the United Daughters of the Confederacy Upson, Georgia Chapter. Includes transcription of Address by J.E.F. Matthews for the Confederate Soldier Monument of Thomaston, Georgia, delivered on May 2, 1908; Upson County Confederate Company rosters.
Book. 40 Pages. Cover w/ handwritten note. Scanned at 600dpi 24/bit tiff. Converted to PDF/A format w/ ABBYY FineReader 12.0. Processed by Dallas Suttles, dasuttles@valdosta.edu, 20170520. Scanned from an original print. MS/63 Box 2, Folder 10. Valdosta State University Archives and Special Collections
Keywords: Confederate Memorial Day addresses; Personal narratives, Confederate; Confederate States of America--History; Confederate States of America--History--Sources; Confederate States of America--History--Societies, etc; Confederate States of America. Army--Registers; Soldiers' monuments--Southern States; United States--History--Civil War, 1861-1865--Regimental histories